Business Strategy Analysis For Spin-Off and Islamic Banking Growth: Canvas Business Model Approach - Waskin; Rifki Ismal; Yulizar D. Sanrego (CV. Inara, 2022)
(“UUS” – Unit Usaha Syariah) in each conventional bank must begin preparing for spin-offs process following the OJK policy which they must be spin-off before July 2023. However, there are still many “UUS” that need to be spin-off into BUS, where UUS is part of the Islamic Business Unit in every conventional bank (“BUK” – Bank Umum Konvensional).The aim of this paper is to provide a comprehensive analysis of business strategy for supporting the spin-off process “UUS” become “BUS” and business strategy for Islamic banking growth by utilizing the Canvas business model approach. This research was conducted using SWOT analysis methods to confirm the effective business strategies for spin-offs through analysis of existing business strategies at “UUS” with utilizing the nine blocks of Canvas's business model (Customer Segment, Value Proposition, Customer Relations, Channel, Revenue Stream, Main Activity, Main Resources, Major Partners and Cost Structure). The results of this study show that business strategy on